Experimental cervical interspinous ligament pain altered cervical joint motion during dynamic extension movement. (May 2019) - Qu, Ning; Lindstrøm, Rene; Graven-Nielsen, Thomas; Hirata, Rogerio Pessoto
Abstract: Background: Although the cervical interspinous ligament is a potential source of neck pain, the effects on cervical joint motion and pressure pain sensitivity has never been investigated. The understanding of the relationship will broaden our understanding of cervical biomechanics and improve diagnosis and treatment of neck pain. Methods: Fluoroscopy videos of cervical flexion and extension movements and pressure pain thresholds over bilateral C2/C3 and C5/C6 facet joints were collected in fifteen healthy subjects before and after injections of hypertonic and isotonic saline in C4/C5 ISL. The videos were divided into 10 even epochs and the motion of individual joints during each epoch was extracted. Joint motion parameters including anti-directional motion, pro-directional motion, total joint motion and joint motion variability were extracted across epochs. Joint motion parameters and PPTs were compared before and after injection of hypertonic and isotonic saline separately. Findings: Compared with baselines: hypertonic saline injection 1) decreased anti-directional motion and joint motion variability at C4/C5 ( P < 0.05) and increased at C2/C3 ( P < 0.05) during extension; 2) increased total joint motion of C0/C1 during first half range ( P < 0.05) and decreased during second half range of extension, and total joint motion of C2/C3 increased during second half range of extension ( P < 0.05) and; 3) increased pressure pain thresholds over left C2/C3 facet joint ( P < 0.01). Interpretation: The cervical interspinous ligament pain redistributed anti-directional motion between C4/C5 and C2/C3 during dynamic extension and decreased pressure pain sensitivity over the left C2/C3 facet joint. Highlights: Interspinous ligament pain altered cervical joint motion pattern during extension. Anti-directional motion was redistributed from C4/C5 to C2/C3 during extension. Interspinous ligament pain increased pressure pain threshold over left C2/C3 facet joint.